Carbohydrate Accumulation in Different Wheat Cultivars for Elevated Temperature - Soyema Khatun (Research Highlights in Agricultural Sciences Vol. 8, 2023)
Carbohydrate accumulation of three wheat cultivars namely BARI Gom 25, BARI Gom 26 and Pavon 76 due to terminal heat stress were sown on two temperature regimes viz. normal (23\(^°\)C in open field) and elevated (6 ± 1\(^°\)C higher compare to open field mean air temperature in polythene chamber) were created. Elevated temperatures reduced grain filling time by 5 days in BARI Gom 25 and 26 and by 10 days in Pavon 76. Even though there was a larger quantity of soluble sugar in the grain, it was discovered that grain starch synthesis was terminated at 25 days after anthesis (DAA) in Pavon 76 and appeared 5 days later (30 DAA) in BARI Gom 26. The findings show that early failure of sugar conversion to starch, rather than a lack of soluble sugar under elevated temperature conditions, is responsible for shorter grain filling duration and smaller grain size in all wheat cultivars.